Bodipy−Corrole dyad with truxene bridge: Photophysical Properties and Application in Triplet−Triplet Annihilation upconversion. (December 2019) - Che, Yuanyuan; Yuan, Xuemei; Cai, Fangjian; Zhao, Jianzhang; Zhao, Xiaoyu; Xu, Haijun; Liu, Lang
Abstract: Free base corrole can generate triplet state without relying on the heavy-atom effect, however, its absorption in the visible spectral range (430–650 nm) is very weak which makes corrole not an ideal triplet photosensitizer. Herein, we prepared a novel truxene-bridged Bodipy−corrole dyad (B −T −Co ) which have strong, broad absorption in Uv–visible spectral range (300 nm − 676 nm, the maximum molar absorption coefficient is up to 1.09 − 10 5 M− 1 cm− 1  at 426 nm). The dyad showed fast singlet-singlet energy transfer from Bodipy moiety to corrole moiety (2.16 − 10 8  s− 1 ), high strong singlet-oxygen ( 1 O2 ) photosensitizing ability (70%), prolonged triplet state lifetimes (149 μs) and high triplet state energy levels (1.41 eV) as compared to corrole (singlet-oxygen photosensitizing ability: 58%; triplet lifetimes: 116 μs; triplet energy levels: 1.32 eV). Moreover, the dyad used as triplet photosensitizer for triplet−triplet annihilation upconversion, with red excitation at 589 nm, the upconversion emission intensity is higher than the corrole itselef and the upconversion quantum yield (2.57%) increases by ca. 2-folds. Graphical abstract: The energy transfer in Bodipy-Corrole dyad was studied with time-resolved spectroscopies and the application in triplet-triplet annihilation upconversion was studied.Image 1 Highlights: The metal-free corrole was used as a triplet photosensitizer for TTA−UC. A novel truxene bridged Bodipy (as the energy donor) and corrole (as the energy donor) dyad was reported. The dyad has broader absorption range, stronger 1 O2 photosensitizing ability and longer triplet lifetime than corrole. The dyad was used in TTA−UC, the upconvertion quantum yield increases by 2-fold than the corrole.